Chemical engineering visions of the world - World Congress on Chemical Engineering 2001 : Melbourne, Vic.); Darton, Richard; Wood, D. G.; Prince, R. G. H. (Amsterdam ; London : Elsevier, 2003)
This book presents six visionary essays on the past, present and future of the chemical and process industries, together with a critical commentary. Our world is changing fast and the visions explore the implications for business and academic institutions, and for the professionals working in them. The visions were written and brought together for the 6th World Congress of Chemical Engineering in Melbourne, Australia in September 2001. Identifies trends in the chemicals business environment and their consequences Discusses a wide variety of views about business and technology Describes the impact of newly developing technologies.
Preface; Opening AddressChemical Engineering and Tomorrow's World; Chemical Engineering -- The First 100 Years; The Future Shape of the Process Industries; The Chemical Engineer and the Community; Chemical Engineering: The Practice of the Profession "Pace, Price, Perplexities"; Formulation of a Vision: Chemical Engineering in the 21st Century; Commentary on the Visions.
Includes bibliographical references and index.
Keywords: Chemical engineering -- Congresses; Chemical industry -- Congresses; Electronic books; Conference proceedings